Pelatihan Kerajinan Ibu-Ibu PKK dari Limbah Bekas Kemasan Pabrik Kopi Pada PT. Santos Jaya Abadi Menjadi Sebuah Produk Tas dan Tempat Tisu - Ersa Dina Fitaloka; Dessi Fitria Ningsih; Rahayu Mardikaningsih; Nelud Darajaatul Aliyah; Siti Nur Halizah; Fayola Issalillah; Rafadi Khan Khayru; Didit Darmawan; Eli Masnawati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
Women's empowerment is one indication of rising welfare. When women become educated, have property rights, and have the freedom to work outside and earn an independent income, this is a sign of improved household welfare. One of the steps in empowering women in Indonesia is done through PKK activities. Empowering PKK mothers as members of the community and who are also classified as productive labour is vital. The purpose of this empowerment is to develop awareness and independence in business, as well as to expand employment opportunities and increase the knowledge of mothers in Panjunan Village. This alternative was chosen because PKK women in the Panjunan area really need knowledge and skills that can be used as provisions and hone the skills of each individual. This training is expected to complement the knowledge and skills of PKK women in various aspects, and can provide benefits in showing their existence in skills, while equipping themselves to do business which in turn can encourage increased income in the family.